Use of heparosan polysaccharide to enhance drug delivery - DeAngelis, Paul L. (Henry Stewart Talks, 2012)
Drug Delivery Vehicles, Use of stealthy polymers to improve drug cargo pharmacokinetics and fate in the body, Glycosaminoglycan [GAG] Glycosyltransferases, Bifunctional synthases polymerize sugar chains, Chemoenzymatic synthesis; use of enzymes to create defined polymers